Design of a virtual longitudinal observational study in Parkinson's disease (AT‐HOME PD). Issue 2 (22nd December 2020) - Schneider, Ruth B.; Omberg, Larsson; Macklin, Eric A.; Daeschler, Margaret; Bataille, Lauren; Anthwal, Shalini; Myers, Taylor L.; Baloga, Elizabeth; Duquette, Sidney; Snyder, Phil; Amodeo, Katherine; Tarolli, Christopher G; et al.
Abstract: Objective: The expanding power and accessibility of personal technology provide an opportunity to reduce burdens and costs of traditional clinical site‐centric therapeutic trials in Parkinson's disease and generate novel insights. The value of this approach has never been more evident than during the current COVID‐19 pandemic. We sought to (1) establish and implement the infrastructure for longitudinal, virtual follow‐up of clinical trial participants, (2) compare changes in smartphone‐based assessments, online patient‐reported outcomes, and remote expert assessments, and (3) explore novel digital markers of Parkinson's disease disability and progression. Methods: Participants from two recently completed phase III clinical trials of inosine and isradipine enrolled in Assessing Tele‐Health Outcomes in Multiyear Extensions of Parkinson's Disease trials (AT‐HOME PD), a two‐year virtual cohort study. After providing electronic informed consent, individuals complete annual video visits with a movement disorder specialist, smartphone‐based assessments of motor function and socialization, and patient‐reported outcomes online. Results: From the two clinical trials, 226 individuals from 42 states in the United States and Canada enrolled. Of these, 181 (80%) have successfully downloaded the study's smartphone application and 161 (71%) have completed patient‐reported outcomes on the online platform. Interpretation: It is feasible to conduct a large‐scale, international virtual observational study following the completion of participation in brick‐and‐mortar clinical trials in Parkinson's disease. This study, which brings research to participants, will compare established clinical endpoints with novel digital biomarkers and thereby inform the longitudinal follow‐up of clinical trial participants and design of future clinical trials.